Charge-controlled swelling gradients at 200-µm resolution in an open-porous polymeric structure for compliance modulation - Sarokin, Yauheni; Aabloo, Alvo; Must, Indrek (Frontiers in Materials, 2023)
Plants combine active and passive liquid-mediated mechanisms across broad spatial and temporal scales, inspiring technological developments, in particular involving variable stiffness. Swelling is of particular interest due to the abundance of plant models and applicable (bio)materials, yet existing control by environmental humidity sorption limits its applications. This work combined swellable polymeric structures with electroactive control: we considered an open-porous polymeric laminate that hosted an electrokinetic medium also co-acting as a swelling agent for the same polymer. A constant volume of liquid (an electrolytic solution) was electrokinetically pumped between the symmetrical laminate's interior and surface layers: as the second moment of inertia increases from the centre to the surface, the pumping of liquid towards the surface decreases the laminate's bending stiffness, and vice versa. Ion electrosorption on high-specific-surface-area carbon electrodes, deposited in three layers in the laminate by simple additive spraying, facilitated the ion current necessary for the electrokinetic pumping. Flexural rigidity of the 400 µm thick laminate varied by 7% in response to 2-V input, evidencing swelling gradients forming at half-laminate (i.e., 200-µm) resolution. Charge-driven local rearrangement of liquid allows for broader adoption of bioinspired (and biological) porous architectures, where the channels are defined collectively, not individually as in, e.g., soft lithography. Sub-mm resolution and low-voltage control of liquid offer a high level of integration at minimal assembly, positioning active swelling as a promising solution for wearable and bioinspired soft robotic applications.